Head-to-head comparison of SARS-CoV-2 antigen-detecting rapid test with professional-collected nasal versus nasopharyngeal swab. Issue 5 (6th May 2021) - Lindner, Andreas K.; Nikolai, Olga; Rohardt, Chiara; Burock, Susen; Hülso, Claudia; Bölke, Alisa; Gertler, Maximilian; Krüger, Lisa J.; Gaeddert, Mary; Tobian, Frank; Lainati, Federica; Seybold, Joachim; et al.
Antigen-detecting rapid diagnostic tests (Ag-RDTs) are likely to play a substantial role in innovative testing strategies for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) [1, 2]. Currently, most Ag-RDTs require nasopharyngeal (NP) sampling performed by qualified healthcare professionals. Nasal sampling would enable scaling of antigen testing strategies. The term nasal sampling is often not used uniformly, but can be differentiated as either anterior nasal sampling (entire absorbent tip of the swab, usually 1 to 1.5 cm, inserted into nostril), and nasal mid-turbinate (as described below) [3]. Professional nasal sampling is a reliable alternative to nasopharyngeal sampling when using a WHO-listed SARS-CoV-2 antigen-detecting rapid test. This less invasive method needs less training to facilitate rapid scaling of testing strategies. https://bit.ly/3pEVlUL